Determination of Safe Level of Benzene Concentration in Mechanics Workshop “X” Tembalang Semarang - Aisy Rahmania1, Abdul Rohim Tualeka1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vehicles are used in community in a large number and being repaired in motorbike repair shops. The repaired motorbike at the workshop has the potential to provide benzene exposure to the mechanic, so the mechanic was also at risk of experiencing health problems due to benzene exposure. This study aimed to determine the safe concentration of benzene in Workshop X Tembalang, Semarang. This study was a descriptive research. The population in this study were mechanics at Locations 1 and 2, totally 18 people. The results of this study were quantitatively analyzed to determine the safe concentration of benzene for workers obtained from the benzene concentrations in the workplace, worker height, worker weight, rats weight, worker respiration rate, length of work, worker body surface area, mice body surface area, highest dose of toxin without effect on experimental animals (NOAEL), Km factor in animals (Animal Km), Km factors in workers (Human Km), and safe limit dose for workers (RfC). The measurement of benzene concentration at Location 1 was 0.28 ppm and Location 2 was 0.19 ppm, which means that the benzene concentration was still below the Threshold Value according to Minister of Manpower Regulation Number 13 in 2011 amounting to 0.5 ppm. This research showed that the safe limit value was 0.023 ppm. Based on the minimum risk level, the concentration of benzene everyday that can cause acute effects was 0.009 ppm and that can cause chronic effects was 0.003 ppm. These standards indicate that the concentration of benzene in the workshop has the potential to have a negative impact on the health of workers. Recommendations to workshop owners and mechanics are to periodically monitor benzene levels in the air, use personal protective equipment by all mechanics and if needed the workshop owner can conduct a health check-up for all mechanics.